Peningkatan Teknik Pounding Terinspirasi Happa-Zome dalam Kegiatan Pembuatan Tekstil Ramah Lingkungan di PPSA “Taruna Yodha” Sukoharjo - Affanti, Tiwi Bina; Santoso, Ratna Endah; Sarwono, Sarwono -; Josef, Adji Isworo; Utami, Lira Anindita (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
This community service is carried out with the participation of PPSA “Taruna Yodha” children-in-care, in Sukoharjo, Central Java. By creation of textile products, the activity that incorporates an eco-friendly production process inspired by the Japanese Happa-zome technique (manual leaf-printing decoration technique) is chosen and improved for motivating environmental awareness while strengthening the entrepreneurial capacity of the beneficiaries. The service program is conducted by (in)direct presentation and mentoring, a participatory and iterative process from the beginning to the end. Within the program, design survey activity in the form of exploring the potential of nature is to be involved for introducing the surrounding natural environment while collecting leaf material. The results are; (1) Providing environmental awareness for beneficiaries through textile-making, (2) Happa-zome technique for interior textile product development, (3) Entrepreneurial program covering story-making and on-line marketing strategy